THE EFFECT OF USING NUMBERED HEADS TOGETHER COOPERATIVE LEARNING MODEL TOWARDS STUDENTS’ READING COMPREHENSION ON RECOUNT TEXT OF GRADE EIGHT AT MADRASAH TSANAWIYAH NURUL FALAH - Sartika Sari; Destri Wahyuningsih (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
The purpose of this research were to find out is there any significant effect of the cooperative learning model Numbered Heads Together toward Students’ Reading Comprehension on Recount Text of Grade Eight at Madrasah Tsanawiyah Nurul Falah Airmolek. Based on the research, it was founded that some of the students lack active, concentrated, and motivated in learning English. They had difficulties in comprehending the reading test. They could not get information about the context. Beside that, they lack of item the vocabulary. This is an Experiment research. This research was carried out at Madrasah Tsanawiyah Nurul Falah Airmolek. It was started on April, 17th to May, 24th 2019. The subject of this research was students of grade eight at Madrasah Tsanawiyah Nurul Falah Airmolek. The sample of this research was 71 students which consist of 37 students as the control class in grade eight B and 36 students as the experimental in grade eight C with using a random sampling technique. The test was used in data collection technique. The tests were given to both classes. The research finding revealed that the average score was 65.45 in the control class and 59.27 in the experimental class. After applying the model in the experimental class, the score of the post-test was 72.61. Meanwhile, the score for the control class which was not given the treatment was 67.14. This research was analyzed with using Independent Sample Test (T-test), it was obtained by comparing to (t-obtained) to tt (t-table). From df= 71, it is found that the level of significance of 5% is 2.00 and the level of significant 1% is 2.65. It can be seen that 2.002.65. It means that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. It can be concluded that there is a significant effect of using Number Heads Together Cooperative Learning Model towards students’ reading comprehension on recount text of grade eight at Madrasah Tsanawiyah Nurul Falah Airmolek.